Hayek: A Collaborative Biography Part XII: Liberalism in the Classical Tradition, Austrian versus British - Leeson, Robert (Archival Insights into the Evolution of Economics,, 2018)
F.A. von Hayek (1899-1992) was a Nobel Prize winning economist, famous for promoting an Austrian version of classical liberalism. The multi-volume Hayek: A Collaborative Biography examines the evolution of his life and influence. Two concepts of civilization revolve around power - should it be separated or concentrated? Liberalism in the non-Austrian classical tradition remains fearful of power concentrated in the hands of government, labour unions or corporations; Red Terrorists sought to monopolize power to liquidate enemies and competitors as a prelude to utopia (the 'withering away of the State'); and behind the 'slogan of liberty,' White Terror promoters (Mises and Hayek) sought to concentrate power in the hands of a 'dictatorial democracy' where henchmen would liquidate enemies, and - 'guided' by 'utopia' (the 'spontaneous' order) - follow orders from their social superiors. This volume, Part XII, examines the 'free' market Use of Knowledge in Society; examines the foundations of 'free' market educational credentials; and asks whether those funded by the tobacco industry and the carbon lobby should be accorded 'independent policy expert' status. .